The Idea of Human Rights - Brienza, Paul (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2014)
The idea of human rights entered global discourse, in a large fashion, in the 20th century. The adoption of the United Nations Charter and the Universal Declaration of Human Rights at the end of the Second World War has ushered in an era of human rights discourse. This discourse, however, was overshadowed by the long Cold War. With the fall of the Berlin Wall, the global dream of unity, under a common concern and commitment to human rights, has remained a calling card of the last quarter century.The purpose of this issue of Theoria and Praxis is to examine some of the most important elements of this re-orientation as well as the significant contradictions and obstacles in the path of such an aspiration as ‘global human rights.’ The papers presented here offer readers a poignant perspective on the issue. For example, is human rights, as both a theoretical discourse and practical enterprise, inherently ‘Western?’ If so, is this endeavor another stage in the spread of Western ideas and culture? Can it be categorized as another form of neo-colonialism? Further, are human rights an inherently ‘liberal’ discourse? And, if so, how do we make its concerns spread beyond the realm of strictly political rights to economic and social rights?Other papers in this collection, seek to examine the theoretical groundings of human rights. The main question here revolves around the chasm that separates human rights as an ideal, embodied in international law as well as the philosophies of speculative reason, from the reality of our lives. That is, how and in what manner, can this discourse loose its exclusively formal and abstract character and become something full of the content of lived experience?We cordially invite readers to take up the mantle of the human rights debate, along with our authors. For in this debate are to be found the main issues of concern for the young 21st century: namely, can we live under an umbrella of international law? And, what is the possible form of global unity? Lastly, how does globalization impact the fight for individual rights? That is, can we live both globally and locally?